Concept of limit stress for the tensile behavior of carbon fiber composite tows. (15th November 2020) - Kant, Matthew E.; Crabtree, Joshua D.; Young, Stephen; Penumadu, Dayakar
Abstract: A new criterion, the limit stress, is presented for characterizing the mechanical performance of carbon fibers via the impregnated tow method. A description of the method and its underlying connection to actual single carbon fiber mechanical performance is given and an initial demonstration of the technique is implemented. For implementation, a commercial 24k tow carbon fiber was interrogated mechanically, and prepared using two independent approaches, resulting in two cross-sectional geometries; flat (ribbon) and round. The average ultimate failure stress and average limit stress from round to flat were reduced by 5.76% and 16.8%, respectively. Hence, the limit stress approach is between 2–3x more sensitive to induced variations in tow performance compared to the peak load approach. This method gives critical insight to the nuances of carbon fiber performance, important to the understanding of fiber types (for example low-cost carbon fibers) and coupled fiber surface optimization.